El uso de nanofertilizantes impacta en el porcentaje de micorrizacion y rendimiento de soja - Ciacci, María Belén; Giachero, María Lorena; Rosa, M.; Silva, A.G. (Asociación Argentina Ciencia del Suelo (AACS), 2022)
Poster